“To give life is a journey through the unknown”: an ethnographic account of childbirth experiences and practices in Southern Benin - Armelle Akouavi Vigan; Jean-Paul Dossou; Christelle Boyi; Lydie Kanhonou; Lenka Benova; Thérèse Delvaux; Charlotte Gryseels (Sexual and Reproductive Health Matters)
In Benin maternal mortality remains high at 397 deaths per 100,000 live births, despite 80% of births being attended by skilled birth attendants in health facilities. To identify childbirth practices that potentially contribute to this trend, an ethnographic study was conducted on the use of biomedical and alternative health services along the continuum of maternal care in Allada, Benin. Data collection techniques included in-depth interviews (N = 83), informal interviews (N = 86), observations (N = 32) and group discussions (N = 3). Informants included biomedical, spiritual and alternative care providers and community members with a variety of socioeconomic and religious profiles. In Southern Benin alternative and spiritual care, inspired by the Vodoun, Christian or Muslim religions, is commonly used in addition to biomedical care. As childbirth is perceived as a “risky journey to the unknown”, these care modalities aim to protect the mother and child from malevolent spirits, facilitate the birth and limit postpartum complications using herbal decoctions and spiritual rites and rituals. These practices are based on mystical interpretations of childbirth that result in the need for additional care during facility-based childbirth. Because such complementary care is not foreseen in health facilities, facility-based childbirth is initiated only at an advanced stage of labour or at the onset of a perceived immediate life-threatening complication for the mother or baby. Programmes and policies to reduce maternal mortality in Benin must seek synergies with alternative providers and practices and consider the complementary and integrated use of alternative and spiritual care practices that are not harmful.